Féminismes et luttes contre l'homophobie: de l'apprentissage à la subversion des codes - Bard, Christine; Bastien Charlebois, Janik; Boisclair, Isabelle; Bourque, Dominique; Charbonneau, Amélie; Deshoulières, Étienne; Horincq Detournay, Rosine; Laprade, Bruno; Lebreton, Christelle; Maiorano, Sabrina; Ricard, Nathalie; Vallerand, Olivier (Université du Québec à Montréal, Institut de recherches et d'études féministes, 2016)
En 1903, à Berlin, Anna Rueling appelait le mouvement homosexuel et le mouvement des femmes à s’entraider puisque tous deux luttaient pour la liberté et l’autodétermination individuelle. Plus d’un siècle plus tard, quelles convergences peut-on observer entre féminismes et luttes contre l’homophobie? Sur le plan de la pensée, quels rapprochements contemporains peut-on établir entre le champ des études féministes et celui de la diversité sexuelle et de genre? Comment s’articule l’intersection entre ces deux systèmes de différenciation hiérarchique que sont le sexisme et l’hétérosexisme ? Quels théories et concepts y circulent de manière transversale, et avec quelles redéfinitions? Ces questions ont guidé l’organisation du colloque «Féminismes et luttes contre l’homophobie: zones de convergence» tenu dans le cadre du congrès de l’ACFAS 2014 à l’Université Concordia, Montréal, le 16 mai 2014.
disponible en ligne https://oic.uqam.ca/publications/publication/feminismes-et-luttes-contre-lhomophobie-de-lapprentissage-a-la-subversion-des-codes
Keywords: amériques; approches et analyses; corps; cours; discipline; droit; empowerment; europe; france; homophobie; lesbianisme; pol5185; politique; pornographie; premier cycle; queer; québec; régions géographiques; science politique; science politique et droit; sciences humaines; sexualité; sociologie; thématiques; violences; violences contre les femmes*; violences sexistes et sexuelles

Sur le façonnement international des causes liées à la sexualité - Broqua C.; Fillieule O.; Roca I Escoda M. (Critique Internationale, 2016)
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; LGBTQIA2+; approches et analyses; cours; discipline; discours dominant; droit; europe; histoire et politique; identités LGBTQIA2+; occident; premier cycle; périodes historiques; queer; régions géographiques; science politique et droit; sexualité; shm4000; systèmes d'oppressions; thématiques

Law Reform, Lesbian Parenting, and the Reflective Claim - Leckey, Robert (Social & Legal Studies, 2011)
The article aims to complicate efforts to make law fit or catch up to social practices. It scrutinizes the ‘reflective claim’ using the case study of recognition of parenting by lesbian couples. Reforms in the United Kingdom’s Human Embryology and Fertilisation Act 2008 and the Canadian province of Quebec’s civil code are compared with empirical work from the social sciences on lesbians’ family practices. The reflective claim rests on problematic ideas about social practices and law. Since law is always blunt and incomplete, choices must be made as to which practices it should aim to recognize. Furthermore, the impact of heterosexist and homophobic conditions on lesbian families means that observable practices may not be a suitable model for gay-affirmative reforms. As advanced in the literature, the reflective claim overlooks law and society’s complex interaction, including how reform will not merely reflect but also alter practices. It fails to do justice to law reform’s normative character, obscuring its costs and positive potential
Keywords: 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; amérique du nord; amériques; angleterre; approches et analyses; canada; corps; cours; discipline; discours dominant; droit; droit des femmes*; europe; hétérosexisme; identités LGBTQIA2+; inégalités; maternité; parentalité; premier cycle; périodes historiques; queer; québec; régions géographiques; science politique et droit; sciences humaines; soc2264; sociologie; systèmes d'oppressions; thématiques

Inside the academy and out: lesbian/gay/queer studies and social action - Ristock, Janice L.; Taylor, Catherine G. (University of Toronto Press, 1998)
Inside the Academy and Out demonstrates that the pedagogical and theoretical insights offered by lesbian/gay/queer studies can have relevance to a broader social sphere. The essayists represented here come from a wide range of disciplines, including English, education, philosophy, sociology, and women's studies. Their essays are divided into two broad areas: 'Pedagogy and Research' and 'Spheres of Action.' Taken together, they explore teaching and research theory, examining their implications in areas such as AIDS education, social services, law reform, and popular culture.
Section: xi, 365 pages ; 24 cm
Keywords: 1900-1999; 1990-1999; LGBTQIA2+; approches et analyses; cours; discipline; droit; ethnographie; intersectionnalité; justice sociale; militance; premier cycle; pédagogie; périodes historiques; queer; santé; science politique et droit; sciences de l'éducation; sciences humaines; sexologie; soc2014; thématiques; violences